Проблемы математической подготовки школьников в логике ЕНТ и пути их решения - Ядрова, С.В. (My University, 2013)
The transition to international standards of education, and the Unified National Test (UNT) and is the first stage of this transition poses some other problems to students in comparison with the previous system of knowledge control. Unified National Testing in general and in particular, mathematics, brought into our educational space has its own advantages and. To draw weakness in to the strength, the teacher who prepares students for the exam, you first need to know about the format and structure of the UNT, procedures pecubrities of its implementation. UNT helps to solve important problem to the teacher, as the development of teaching technologies and organization of the final revising, providing the graduates to demonstrate their knowledge no lower its annual mark.